Best Answer

You write: --> divide both sides by 6 --> cross out the 6's --> here's y! :)

55 = 6y --> 55/6 = 6y/6 --> 55/6 = y --> 9.16667 = y

Q: How do you solve 55 equals 6y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6y - 5 = -5; so 6y = -5 + 5; so 6y = 0; so y = 0

6y equals 5y plus 2y can be simplified to 6y = 7y. To solve for y, subtract 7y from both sides of the equation, which gives 6y - 7y = 0. This simplifies to -y = 0, or y = 0.

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

(A) x + 6y = 19 (B) -x + 6y = 17 (A)+(B): 12y = 36 so that y = 3 Substituting this value of y in (A), x + 18 = 19 so x = 1.

4x+6y=62 -6x+6y=-18 what is the ordered pair

Related questions

6y - 5 = -5; so 6y = -5 + 5; so 6y = 0; so y = 0

Not sure if you mean 7x 6y as in 7*6y=126, where * means "multiplied by" and you must solve for y or if you mean that we must solve for both x and y, but the answer to the part where you are solving 7*6y=126 is 3.

x=6y-4x=-2y+28Substitute (6y-4) for x in the second equation and solve for y:6y-4=-2y+288y=32y=4Then solve for x:x=6(4)-4=20(20,4)

its just a line, there are many answers that would work -12x-6y=0 -12x=6y x=-y/2 y=-2x

6y equals 5y plus 2y can be simplified to 6y = 7y. To solve for y, subtract 7y from both sides of the equation, which gives 6y - 7y = 0. This simplifies to -y = 0, or y = 0.

10y= 6y+5+3y 10y=6+9y y=6

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

(A) x + 6y = 19 (B) -x + 6y = 17 (A)+(B): 12y = 36 so that y = 3 Substituting this value of y in (A), x + 18 = 19 so x = 1.

y-3x+6y=12 7y=3x+12 y=3x/7 +12/7

x = 6 and y = -2

Watch closely:5x - 6y = 13Subtract 5x from each side of the equation:-6y = 13 - 5xDivide each side by -6 :y = 5x/6 - 13/6

4x+6y=62 -6x+6y=-18 what is the ordered pair